Qira'at Imam Ibn 'Amir In The Views Of Imam Al-Tabariyy And Imam IBn Mujahid : An Analytical Study - Yasir Hamad Mahmood
Scholars have generally agreed on three conditions for the validity of qirā’āt: authentic and sound sanad, congruence with ʿUthmānic orthography, and eloquent Arabic and proper grammar. Ibn Mujāhid had included Qirā’ah Ibn ʿĀmir as one of the seven qirā’āt mutawātirah. On the other hand, al-Ṭabariyy rejected the qirā’ah, as explicitly stated in Jāmiʿ al-Bayān. This conflict of opinion persisted despite al-Ṭabariyy’s strong influence on Ibn Mujāhid as a teacher. Against this problem, the research sought to accomplish four objectives: (i) to discuss the development of seven qirā’āt before and during the lifetime of Ibn ʿĀmir; (ii) to analyze the mutawātir concept of both al-Ṭabariyy and Ibn Mujāhid; (iii) to discuss the factors behind the rejection or approval of Qirā’ah Ibn ʿĀmir by al-Ṭabariyy and Ibn Mujāhid; and (iv) to evaluate the chain, ṭuruq, and uṣūl of Qirā’ah Ibn ʿĀmir. The research employed the qualitative methodology and used the descriptive-analytical approach to accomplish these objectives. It revealed a number of important findings: first, the number of qirā’āt had exponentially grown since the era of the companions up to next two generation. The number of qirā’āt, however, gradually dwindled as qirā’āt seekers shift their focus, and because some scholars compiled only certain qirā’āt into their books, leaving the impression that those were the only mutawātir recitations. Second, al-Ṭabariyy’s conception of mutawātir in qirā’āt is almost similar to that of hadith scholars. Additionally, he did not suffice with the three abovementioned conditions, but also added that a qirā’ah is accepted if it is a subject of consensus and popular among reciters. Ibn Mujāhid’s concept is almost similar: a mutawātir recitation is that which is a subject of consensus among scholars and the laymen and is read by the entire populace of a given province. Third, al-Ṭabariyy rejected Ibn ʿĀmir’s qirā’ah on the basis that its sanad is untrustworthy, and that the companion from whom the variant was narrated, ʿUthmān, had never been reported to have taught qirā’ah to anyone. Ibn Mujāhid, meanwhile, accepted it as it was a prevalent recitation in Kufah. However, he still criticized some of its aspects that contravene proper Arabic grammar.